Porous single crystalline-like titanium dioxide monolith with enhanced photoelectrochemical performance - Liu, Kaipeng; Cheng, Fangyuan; Luo, Yunfei; Liu, Ling; Wang, Changtao; Xie, Kui; Luo, Xiangang (Frontiers in Materials, 2023)
Macro-sized porous single crystalline-like (PSC-like) TiO2 is endowed with unique structural advantages due to its structural consistency and porosity in a large area, which would significantly enhance its photoelectrochemical function. However, there are significant technical challenges in the growth of porous single crystalline-like monoliths. The consistency of structure dominates the structure so that the grain boundary is reduced to the minimum, which is in contradiction with the three-dimensional percolation structure. Here we report a lattice reconstruction strategy based on solid-solid transformation to grow porous single crystal-like anatase TiO2 dominated by (200) and (101) facets at 2 cm scale. In comparison with the traditional definition of porous single crystal, it has two different lattice orientations, but still has good photoelectrochemical properties. The band gap engineering introduces Ti3+ gap into the lattice to generate TinO2n−1 with Magneli phase, limiting the created active structure to the lattice with two-dimensional surface, which would open a new avenue to create highly active surfaces to capture photons and transport electrons stably. The PSC-like TinO2n−1 provides enhanced exciton lifetime (3–5 ns) as a photocatalytic catalyst and shows significant visible light absorption. The independent PSC-like TinO2n−1 delivers high photocurrent of 1.8–5.5 mA · cm−2 at room temperature and does not decay for 10 h.